2019
DOI: 10.1016/j.childyouth.2018.11.036
|View full text |Cite
|
Sign up to set email alerts
|

Romantic involvement and adolescents' academic and psychosocial functioning in Chinese societies

Abstract: This study explores the effects of romantic involvement and dating behaviors on adolescent academic and psychosocial functioning in Chinese societies, where adolescent dating is generally discouraged and believed to bear adverse outcomes. Adolescents (male = 48.6%; Mean Age = 15.20 years) from Taiwan (N = 1,081) and Mainland China (N = 684) were recruited through stratified sampling to complete self-report surveys oned their academic performance, depressive symptoms, self-esteem, relationship status, and gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…This research also found higher rates of anxiety and depression among those not in a relationship throughout young adulthood, but this is not true of those not in a relationship in adolescence. Previous research found that adolescents in romantic relationships demonstrate higher levels of depressive symptomatology than those who are not [49,59,60], though other studies observed that these relationships may enhance adolescents' emotional well-being [21,22]. The effect of having been in a romantic relationship during adolescence or not has not yet yielded any conclusive results.…”
Section: Discussionmentioning
confidence: 94%
“…This research also found higher rates of anxiety and depression among those not in a relationship throughout young adulthood, but this is not true of those not in a relationship in adolescence. Previous research found that adolescents in romantic relationships demonstrate higher levels of depressive symptomatology than those who are not [49,59,60], though other studies observed that these relationships may enhance adolescents' emotional well-being [21,22]. The effect of having been in a romantic relationship during adolescence or not has not yet yielded any conclusive results.…”
Section: Discussionmentioning
confidence: 94%
“…Using a measure and scoring criteria based on Western cultures, secure attachment was a normative form of adult romantic attachment in most (79%), but not in all, the cultures examined [11]. More specifically, attachment behaviors viewed as insecure avoidance in Western cultures appear to be normative in Taiwanese culture, and the development trajectories of romantic relationship and dating behaviors may be different in Chinese cultures (for example, see Li et al [12]). Wang and Mallinckrodt [13] report Taiwanese participants as scoring higher on insecure anxiety items than their American counterparts.…”
Section: Cross-cultural Perspectives On Adult Romantic Attachmentmentioning
confidence: 99%
“…Cross-gender friendship provides opportunities to connect with potential romantic partners, or the friendship transitions into romance. Early romance has been found in some research to be negatively related to mental health, such as a higher level of depression and lower self-esteem (Li et al, 2019; Soller, 2014). Related to this, even when no actual romance emerges from a cross-gender friendship, it may potentially encounter prejudice or social pressure from other peers, or even teachers; early romance is stigmatized and forbidden in Chinese schools (Basu et al, 2017; Liu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%